Improvement of facilities layout planning related with safety: a case study at quarry - Tajurahim, Nurul Ainina Nadhirah; Mahmood, Salwa; Marsi, Noraini; Raja Mamat, Tengku Nur Azila (Penerbit UTHM, 2022)
Quarrying is valuable to society because its products are used to build roads, buildings, and other infrastructures that people depend on. The condition or environment and safety in the workplace especially in quarry industries should always pay attention to avoid any injuries, accidents, or any conflicts which at least reduces the seriousness of the conflict. The purpose of this study is to improve the workflow of the production in the company. Also aimed to study the workflow of production and analyzes the safety issue regarding the workplace. This study focused on the improvement of the factory design in XYZ Quarry product Sdn. Bhd related with safety. The improvement of layout involved the minimization of transportation cost, the relevant distance and time need is 3360 tons per day, and relocated the structure of the production process. The results are also concerned with improving safety in the workplace. In addition, the improvement of layout can reduce the cost of production. Besides, the safety improvement can help to reduce the medical cost for workers’ health care and improve the well-being of the workers.